Selaghian Traditional Sanctions upon a Perspective of Islamic Law (Study on Serawai Community in Air Nipis District, South Bengkulu Regency) - Tendra Hernata; Toha Andiko (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
This study discusses the issue of the application of selaghian customary sanctions to the Serawai people of South Bengkulu as well as examines the opinion of Islamic law on these sanctions. This study uses a qualitative method with a descriptive normative legal approach, to unravel the facts found in the f ield (field research). Based on the data collected through observation and in-depth interviews in the field, it was found that the form of selaghian that is still being practiced is selaghian sebambangan, a type of selaghian performed by a couple (male and female) with both of them secretly running away from the house with no friends, going to the house of a local traditional leader, then being told by someone else to tell the couple’s parents, to pick up the couple and marry them off. Customs impose fines that vary according to the severity of the offense committed. In terms of Islamic law, the provision of customary sanctions in the form of ta’zir punishment is legal and may be carried out as a good custom (‘urf shahih) with the aim of causing a deterrent effect for the perpetrators (zawajir).